Advantage of endoscopic submucosal dissection compared with EMR for early gastric cancer - Oka, Shiro; Tanaka, Shinji; Kaneko, Iwao; Mouri, Ritsuo; Hirata, Mayuko; Kawamura, Toru; Yoshihara, Masaharu; Chayama, Kazuaki (Gastrointestinal endoscopy, 2006)
In EMR of early gastric cancer (EGC), en bloc resection reduces the risk of residual cancer. Endoscopic submucosal dissection (ESD) now allows en bloc resection of large EGCs. To retrospectively determine whether ESD is more advantageous than EMR for EGCs. EMR (825 lesions, 711 patients) or ESD (195 lesions, 185 patients) was performed. The en bloc resection rate, histologically complete resection rate, operation time, complications, and local recurrence rate were studied in relation to ulceration. Hiroshima University Hospital. Subjects comprised 896 patients in whom 1020 EGCs were resected endoscopically from 1990 to 2004. In cases without ulceration, en bloc and histologically complete resection rates were significantly higher with ESD than with EMR, regardless of tumor size. The frequency of ulceration did not differ significantly between groups. Average operation time was significantly longer for ESD than for EMR, regardless of tumor size. Also, regardless of ulceration, the incidence of intraoperative bleeding was significantly higher with ESD (22.6%) than with EMR (7.6%). Delayed bleeding did not differ. In cases with ulceration, the incidence of perforation was significantly higher with ESD (53.8%) than with EMR (2.9%). Local recurrences were treated by incomplete EMR (en bloc, 2.9%; piecemeal, 4.4%). No patient experienced recurrence after ESD. ESD increased en bloc and histologically complete resection rates and may reduce the local recurrence rate. Increased operation time and complication risks with ESD in comparison with EMR remain problematic. Special measures are necessary for ESD of ulcerated lesions to reduce the rates of perforation and incomplete resection.